2019
DOI: 10.26911/thejhpm.2019.04.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Cost Gap Between INA CBGs Tariff and Hospital Tariff for Patients with Dengue Hemorrhagic Fever in Ngawi Regional Public Hospital, East Java

Abstract: Background: Dengue Hemorrhagic Fever (DHF) has a high cost burden. Payment for hospital treatment was paid by Health insurance (BPJS) with a case based payment method in the era of the National Health Insurance. This method allowed the hospital to gain profit or loss. This study aimed to analyze the factors that influence the differences in Indonesian Cased Based Groups (INA CBGs) with the medical service costs for DHF in Dr. Soeroto hospitals, Ngawi Regency. Subjects and Method:This study used an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…These findings are consistent with previous studies conducted by Rahayuningrum et al (2016), Nelson-Williams et al (2016, Wu et al (2020), and Kuo et al (2018). The finding also supports the study undertaken by Ariwardani et al (2019) which discovered age as the determinant of CRR of inpatient care. However, the relationship between gender and CRR was not found in this study, and thus, the result of this study is not fully aligned with previous literature (for instance Wu et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with previous studies conducted by Rahayuningrum et al (2016), Nelson-Williams et al (2016, Wu et al (2020), and Kuo et al (2018). The finding also supports the study undertaken by Ariwardani et al (2019) which discovered age as the determinant of CRR of inpatient care. However, the relationship between gender and CRR was not found in this study, and thus, the result of this study is not fully aligned with previous literature (for instance Wu et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Prior studies have confirmed that LOS determines inpatient care cost (Rahayuningrum et al, 2016;Ariwardani et al, 2019;Aljunid and Jadoo, 2018;Nelson-Williams et al, 2016;Wu et al, 2020;Kuo et al, 2018) and variation of hospitalisation cost (Xu et al, 2020). For instance, Kuo et al (2018) compared models to predict the medical costs of spinal fusion surgery in Taiwan.…”
Section: 33mentioning
confidence: 98%
See 2 more Smart Citations
“…The study of Tamtomo Hospital type, use of ICU, and length of stay, are important determinants of hospital inpatient cost( (Tamtomo & Murti, 2018). Difference in INA CBG rates and hospital medical service costs were affected by the class of care, length of stay, age, blood transfusion, comorbidity and complications (Ariwardani et al, 2019).…”
Section: Strengths Limitationsmentioning
confidence: 99%